An approach towards the development of an inclusive subject environment using additive manufacturing technologies - Lotoshynska, Nataliia; Popova, Solomiya; Irianto, Irianto; Jamil Alsayaydeh, Jamil Abedalrahim (Institute of Advanced Engineering and Science, 2024)
This research aims to identify the principles of designing the objects of the inclusive environment with the employment of additive manufacturing technologies, and to discover methods and techniques for creating an inclusive objective environment using the example of our own development. The results of the survey, which has been directed to investigate the topicality of the problem of inclusiveness in Ukraine and the means of its solution, are presented in the article. In the course of work, the principal peculiarities of three-dimensional (3D) modelling and printing technologies have been established, and promising areas of their application have been proposed. The principles of designing an inclusive objective environment have been detected with the use of photogrammetry and 3D printing, due to which the model can be constructed by considering a person’s individual physical characteristics. Moreover, due to the wide range of materials for 3D printing, various types of objects can be realized. It gives great potential for the employment of 3D printing when designing an inclusive environment and considerably simplifies the manufacturing process while taking the individual characteristics of every person into consideration.